High-order interpolation between adjacent cartesian finite difference grids of different size - Figueroa, Alejandro (2017)
Nested cartesian grid systems by design require interpolation of solution fields from coarser to finer grid systems. While several choices are available, preserving accuracy, stability and efficiency at the same time require careful design of the interpolation schemes. Given this context, a series of interpolation algorithms for nested cartesian finite difference grids of different size were developed and tested. These algorithms are based on post-processing, on each local grid, the raw (bi/trilinear) information passed to the halo points from coarser grids. In this way modularity is maximized while preserving locality. The results obtained indicate that the schemes improve markedly the convergence rates and the overall accuracy of finite difference codes with varying grid sizes.